Replacement Of Castellated Beam By Tapered Castellation - Dhiraj B. Patil; Prof.Vishwajeet A.Kadlag (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Castellated beam is defined as the beam in which increasing width of beam without increasing the self-weight of beam. Now a day castellated beam is a new technique. A castellated beam is fabricated from a standard steel I-shape by cutting the web on a half hexagonal line down the center of the beam. The two halves are moved across by one spacing and then rejoined by welding. This process increases the width of the beam and hence the major axis bending strength and stiffness without adding additional materials. Due to the opening in the web, castellated beams are more susceptible to lateral-torsional buckling. The main benefit of using a castellated beam is to increase its buckling resistance about the major axis. However, because of the openings in the web, castellated beam have complicated sectional properties, which make it extremely difficult to predict their buckling resistance analytically. In the Castellation process the fabrication of a section with improved section properties from virgin rolled section that is improving moment of inertia, improving depth. There by increase in moment of resistance and controlled on deflection.